Participatory Landscape Design and Water Management—A Sustainable Strategy for Renovation of Vernacular Baths and Landscape Protection in Szeklerland, Romania - Albert Fekete; Ágnes Herczeg; Ning Dong Ge; Máté Sárospataki (Land, 2022)
Szeklerland is a historical-ethnic region located on the eastern border of the Carpathian Basin, in the central region of Romania. In Szeklerland, thanks to its varied topography and a network of small settlements, landscape management is still carried out using traditional methods. Szeklerland is a macro-region rich in natural resources. Among its natural treasures, the mineral water springs with healing properties are of particular importance: around 40 percent of Romania’s mineral water resources are found here. This richness in hydrogeological features is due to the fact that the post-volcanic activities in the young tertiary mountain ranges in the region still produce large quantities of carbon dioxide, which dissolves beneficial minerals from the earth. When dissolved in water, these minerals produce mineral waters that can be used to cure various types of diseases. For centuries, the medicinal properties of the mineral waters of Szeklerland have been regularly used by the local population. In addition to their consumption, small and larger vernacular baths were built in the settlements with medicinal springs, and their regular use led to the development of a traditional, local cold-water bathing culture in the region. However, the vernacular baths were destroyed in the world wars, and their traditional use was abolished by the apparatus of the 20th century communist regime, which had no respect to natural and cultural heritage. After the political change in 1989, the attention of the society turned back to tradition and values. Alongside (or as part of) nature and landscape conservation initiatives, the reinterpretation and restoration of the intangible and practical values of vernacular baths in Szeklerland also began. Over the past decades, the renovation of vernacular baths, which started as a professional–civic initiative, has grown into an independent heritage conservation programme: dozens of vernacular baths have been renovated in Szeklerland over the past twenty years with public participation initiated and led by professionals. In the course of the renovations, baths used by local communities have been rebuilt using nature- and environment-friendly techniques, materials and in a way that they are also related to the physical environment and the mythology of the region. The project has won prestigious awards both in Romania and internationally, and has become a successful and exemplary movement in landscape heritage conservation.